2016
DOI: 10.1155/2016/1490181
|View full text |Cite
|
Sign up to set email alerts
|

MELAS Syndrome with Cardiac Involvement: A Multimodality Imaging Approach

Abstract: A 49-year-old man presented with chest pain, dyspnea, and lactic acidosis. Left ventricular hypertrophy and myocardial fibrosis were detected. The sequencing of mitochondrial genome (mtDNA) revealed the presence of A to G mtDNA point mutation at position 3243 (m.3243A>G) in tRNA Leu(UUR) gene. Diagnosis of cardiac involvement in a patient with Mitochondrial Encephalomyopathy, Lactic Acidosis, and Stroke-like episodes syndrome (MELAS) was made. Due to increased risk of sudden cardiac death, cardioverter defibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…In recent years, MELAS has been reported to associate with the development of atherosclerotic lesions and cardiovascular diseases 10,31 . While the primary cause of SLEs in MELAS patients remains controversial, factors such as mitochondrial cytopathy, mitochondrial angiopathy and non-ischaemic neurovascular cellular mechanism, or combined, have been regarded as key contributing factors to disease onset and progression 32 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, MELAS has been reported to associate with the development of atherosclerotic lesions and cardiovascular diseases 10,31 . While the primary cause of SLEs in MELAS patients remains controversial, factors such as mitochondrial cytopathy, mitochondrial angiopathy and non-ischaemic neurovascular cellular mechanism, or combined, have been regarded as key contributing factors to disease onset and progression 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported many mitochondrial mutations causing classic MELAS without any detectable phenotypic specificity [88,89]; exceptional renal diseases were detected in association with m.3243 and m.13513G>A as a first manifestation of MELAS [90,91]. Furthermore, MELAS m.3243 was associated with uncommon presentations such as cardiac and ketoacidosis [92,93].…”
Section: Discussionmentioning
confidence: 99%
“…1 Several other MELAS patients with a PFO have been reported. 6 For example, PFO has been reported in a 41 year-old male with MELAS due to the variant m.3243A > G in MT-TL1. 6 No mention is made of what treatment the patient received for the three "ischemic" strokes.…”
Section: Stroke-like Lesions Should Not Be Mixed Up With Ischemic Str...mentioning
confidence: 99%
“…6 For example, PFO has been reported in a 41 year-old male with MELAS due to the variant m.3243A > G in MT-TL1. 6 No mention is made of what treatment the patient received for the three "ischemic" strokes. Has he ever had thrombolysis or thrombectomy?…”
Section: Stroke-like Lesions Should Not Be Mixed Up With Ischemic Str...mentioning
confidence: 99%